Extracytoplasmic markers of human oocyte quality - Ebner, T.(Landes- Frauen- und Kinderklinik, Linz (Austria)) (Journal of mammalian ova research, 2009)
Within growing follicles oocytes gradually acquire developmental competence to further support early embryonic development. This process is intrinsically linked to folliculogenesis. Thus, the fate of the germ cell depends on the health of the developing follicle, e.g. its vascularization, oxygen content and cumulus cell characteristics. Consequently, gametes of varying quality are harvested after follicular puncture. This review focuses on extracytoplasmic anomalies that should clearly be distinguished from intracytoplasmic ones. In detail, all relevant dysmorphisms related to the zona pellucida and perivitelline space will be discussed. Interestingly, some correlation can be found between extracytoplasmic dysmorphisms and fertilization and preimplantation development. Since genetic constitution is not affected by anomalies of the outer shell, it is postulated that it occurs in the late stages of maturation.